State dependence in Canadian welfare participation - Jörgen Hansen; Magnus Lofstrom; Xuelin Zhang (Institute for the Study of Labor (IZA), 2006)
This paper analyzes transitions into and out-of Social Assistance in Canada. We estimate a dynamic Probit model, controlling for endogenous initial conditions and unobserved heterogeneity, using longitudinal data extracted from the Survey of Labour and Income Dynamics (SLID) for the years 1993-2000. The data indicates that there are substantial provincial differences in social assistance participation. The empirical results indicate that a welfare trap does exist in Canada, but the extent of it varies across provinces. The results also suggest that there is a link between provincial variations in structural and spurious state dependence and regional differences in welfare generosity. In particular, the existence of structural state dependence, or a welfare trap, appears to be more likely in provinces with relatively high benefit levels. One implication of this result is that a change in the welfare benefit structure is not likely to lower participation as significantly among less generous provinces as more generous ones.
Keywords: I30; I38; J18; 330; welfare; state dependence; unobserved heterogeneity; initial conditions; transition; Canada